Lending Standards over the Credit Cycle - Rodano, Giacomo; Serrano-Velarde, Nicolas; Tarantino, Emanuele (Review of Financial Studies, 2018)
We analyze how firms’ segmentation into credit classes affects the lending standards applied by banks to small and medium enterprises over the cycle. We exploit an institutional feature of the Italian credit market that generates a discontinuity in the allocation of comparable firms into the performing and substandard classes of credit risk. In the boom period, segmentation results in a positive interest rate spread between substandard and performing firms. In the bust period, the increase in banks’ cost of wholesale funds implies that substandard firms are excluded from credit. These firms then report lower values of production and capital investments. Received January 22, 2016; editorial decision December 18, 2017 by Editor Robin Greenwood. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.